2023
DOI: 10.1021/acs.jctc.3c01146
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Many-Body Green’s Functions for Molecular Excitation Spectra

Christian Venturella,
Christopher Hillenbrand,
Jiachen Li
et al.

Abstract: We present a machine learning (ML) framework for predicting Green's functions of molecular systems, from which photoemission spectra and quasiparticle energies at quantum many-body level can be obtained. Kernel ridge regression is adopted to predict self-energy matrix elements on compact imaginary frequency grids from static and dynamical mean-field electronic features, which gives direct access to real-frequency many-body Green's functions through analytic continuation and Dyson's equation. Feature and self-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…In Green’s function formalism, the IP and EA are predicted by the quasiparticle energy that directly measures the charged excitation energy. It has been shown that Green’s function approaches substantially improve the accuracy of predicting energy levels over the KS-DFT approach for both occupied and unoccupied states, which are the key quantities to calculate IPs, EAs, and core-level binding energies. ,, , …”
Section: Introductionmentioning
confidence: 99%
“…In Green’s function formalism, the IP and EA are predicted by the quasiparticle energy that directly measures the charged excitation energy. It has been shown that Green’s function approaches substantially improve the accuracy of predicting energy levels over the KS-DFT approach for both occupied and unoccupied states, which are the key quantities to calculate IPs, EAs, and core-level binding energies. ,, , …”
Section: Introductionmentioning
confidence: 99%